(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The inalienable human rights codifications form the basis of human progress. “The goal of this document is to resolve a current and significant problem regarding the convergence of human rights advocacy and the role of ICTs. It will promote efforts to advocate, educate and communicate with others, including media and political stakeholders within and outside the human rights world”[3]. The use of social media can consciously trigger the human rights movement and can also add to their outrage. Any public member or a human rights organisation sends the post, it is reasonably straightforward to explicitly concentrate public attention on social media. The present investigationtried to assess integration of online environment for human rights advocacy.